2016
DOI: 10.1371/journal.pone.0148421
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Influenza and Respiratory Syncytial Virus Infection in Pregnant Women and Infants Under 6 Months in Mongolia: A Prospective Cohort Study

Abstract: BackgroundPregnant women and infants under 6 months are at risk of influenza-related complications. Limited information exists on their community burden of respiratory viruses.Methods and FindingsThis prospective, observational open cohort study was conducted in Baganuur district, Ulaanbaatar, Mongolia during 2013/14 and 2014/15 influenza seasons. Influenza-like illness (ILI) and severe acute respiratory infection (sARI) were identified by follow-up calls twice a week. For those identified, influenza and respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 61 publications
4
33
1
Order By: Relevance
“…Cough, congestion, and sore throat were the most common symptoms among those with PCRconfirmed RSV. In previous studies of ILI, pregnant women with RSV generally reported a mild, febrile illness restricted to the upper airways [14,15]. In our study women who reported fever also had symptoms of LRTI.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Cough, congestion, and sore throat were the most common symptoms among those with PCRconfirmed RSV. In previous studies of ILI, pregnant women with RSV generally reported a mild, febrile illness restricted to the upper airways [14,15]. In our study women who reported fever also had symptoms of LRTI.…”
Section: Discussionsupporting
confidence: 54%
“…An RSV attack rate as high as 13% (10/77) is estimated if calculated using the first ARI episode. This is substantial given that the RSV season in Houston was relatively mild compared to previous years [28], and greater than reported by maternal studies of respiratory illness in Nepal and Mongolia, where RSV accounted for 2% and 2.4% of ARI cases, respectively [14,15]. However, because fever was an inclusion criteria for those studies, and fever occurs in less than one-third of adult RSV infections, these numbers may be an underestimate [29].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Most studies of RSV infection or disease during pregnancy are based on case reports or secondary analyses of influenza vaccine trials [15][16][17]. A recent prospective longitudinal community based study conducted in Houston, Texas, provides additional information regarding the epidemiology of RSV and other respiratory viruses in healthy pregnant women receiving prenatal care at a community obstetrical clinic [18].…”
Section: Clinical Burden Of Rsv In Pregnant Womenmentioning
confidence: 99%